Preparation and Evaluation of Gelatin-Chitosan-Nanobioglass 3D Porous Scaffold for Bone Tissue Engineering - Kanchan Maji; Sudip Dasgupta; Krishna Pramanik; Akalabya Bissoyi (International Journal of Biomaterials)
The aim of the present study was to prepare and characterize bioglass-natural biopolymer based composite scaffold and evaluate its bone regeneration ability. Bioactive glass nanoparticles (58S) in the size range of 20–30 nm were synthesized using sol-gel method. Porous scaffolds with varying bioglass composition from 10 to 30 wt% in chitosan, gelatin matrix were fabricated using the method of freeze drying of its slurry at 40 wt% solids loading. Samples were cross-linked with glutaraldehyde to obtain interconnected porous 3D microstructure with improved mechanical strength. The prepared scaffolds exhibited >80% porosity with a mean pore size range between 100 and 300 microns. Scaffold containing 30 wt% bioglass (GCB 30) showed a maximum compressive strength of 2.2±0.1 MPa. Swelling and degradation studies showed that the scaffold had excellent properties of hydrophilicity and biodegradability. GCB 30 scaffold was shown to be noncytotoxic and supported mesenchymal stem cell attachment, proliferation, and differentiation as indicated by MTT assay and RUNX-2 expression. Higher cellular activity was observed in GCB 30 scaffold as compared to GCB 0 scaffold suggesting the fact that 58S bioglass nanoparticles addition into the scaffold promoted better cell adhesion, proliferation, and differentiation. Thus, the study showed that the developed composite scaffolds are potential candidates for regenerating damaged bone tissue.